Influences of socio-technical factors on public private partnership success in Malaysia - Mohd Som, Rafedzah (2021)
Human resources have been recognised as one of the most critical inputs in many organisational settings, including in the Public Private Partnership (PPP) contexts. The PPP program has been implemented in Malaysia since the 1980s to help the government provide public infrastructure. In a PPP setting, the public and private employees should work as a team to ensure PPP projects' successful implementation. Nevertheless, to date, studies on human-resourcedevelopment-- related issues in inter-organisational settings are still limited, including in the PPP context. The general objective of this research is to examine the relationship between identified socio (facilitator leadership, trust and commitment) - technical (interdependence, communications, and business understanding) factors and PPP success (PPP project success and PPP relational success). Proponents of Socio-technical System Theory have pointed out that the theory’s suitability in improving non-linear working environment issues is still questionable. Therefore, there is a need to examine the PPP working environment issues from an organisational development perspective by applying STS theory. Past literature has pointed out that many factors contribute to an organisation's success or outcome. However, different factors will contribute differently depending on the situation. The theory also underlines the importance of optimising the human and technical input factors in generating organisational output performance and the well-being of the human resources which produce the output. This study is quantitative research adopting purposive sampling. It examines the relationship between the identified socio-technical factors and PPP project success (satisfaction level on PPP project success) and PPP relational success (satisfaction level on PPP relational success). Questionnaires have been developed by adapting past studies measurement items. This research has used different measurement facets, scale anchors, and two kinds of assessment scale to minimise common method variance. This research has analysed the data by employing descriptive, inferential and Structural Equation Modeling (SEM). The Goodness of Fit test has been done in all three SEM analysis levels. The study found that most respondents have a high level of satisfaction on both dimensions of PPP success outcomes. Most respondents agree that there is a high level of leadership, trust, commitment, interdependence, communication and business understanding in the PPP setting. In terms of hypotheses testing, except for commitment and interdependence, other socio-technical factors have at least one positive significant relationship with either satisfaction level on PPP project success or satisfaction level on PPP relational success. The effect size of these relationships is between small to medium. Results also indicate that while facilitative leadership is the major contributor to PPP project success, trust plays an essential role in PPP relational success. This study has contributed to the importance of STS theory in the HRD field by helping to frame the relationship of numerous factors in a non-linear working relationship, such as in a PPP setting. The study has implied the importance of identifying different pertinent factors that need to be intervened to enhance different PPP performance dimensions. However, as this is a cross-sectional quantitative study, a longitudinal qualitative study might better understand the overall level of PPP success and the socio-technical factors that influence it. The research proposed that even though PPP success depends on both the sociotechnical factors that exist in the setting, it is found out that the socio factors play a more pertinent role. Besides facilitative leader and trust, Malaysia PPP players must acknowledge that communication quality and business understanding between the public and the private sectors are vital in achieving PPP success. Strategies must be put in place to enhance the contribution sf these factors towards PPP organisational development success. In conclusion, understanding the importance of socio-technical factors to both dimensions of PPP success will improve PPP program management and decision-making process, including human resource and organisational development. While this research's findings could only be generalised to the intended population, the study itself is a starting point that can be developed further in various PPP settings.